Implementasi E-Commerce di Toko The Familly Collection Desa Panjangsari Kecamatan Gombong Kabupaten Kebumen - Salma Anisa Rinanti; Endang Wahyuningsih (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Retail businesses are increasingly using e-commerce platforms in the quickly changing digital age in order to reach a wider audience, increase operational effectiveness, and satisfy changing customer demands. For The Familiy Collection Store, a fashion and family accessory firm, to be competitive in a changing and difficult market, it must integrate e-commerce in a suitable and well-thought-out manner. The purpose of this study is to evaluate and create an e-commerce platform that is specifically suited to the requirements of The Familiy Collection Store's operations. A user-friendly and responsive interface design, quick and secure integration of a digital payment system, effective and real-time inventory management, and the application of data-based marketing strategies and consumer behavior to boost customer engagement are the primary goals in the development of this platform. In order to gather thorough and precise insights, this study's methodologies include a review of the literature on e-commerce, an analysis of current developments in the digital business, and in-depth interviews with important stakeholders. It is envisaged that by using this strategy, the created e-commerce platform will be able to improve customer happiness, attract a wider audience, fortify the brand, and significantly and sustainably contribute to the long-term success of the business.